ANALISIS PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Multi Instrumentasi Mandiri) - Astriono, Ani; Widowati, Maduretno (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of the work environment on employee performance, analyze the effect of work motivation on employee performance, analyze the simultaneous effect of work environment and work motivation on employee performance. This research is a quantitative descriptive study that serves to explain the description of the object of research through primary data obtained from the distribution of questionnaires, then the data from the questionnaires were analyzed using multiple linear regression analysis with the help of SPSS software. The results of this study indicate that the work environment variable has a significant effect on employee performance, this shows a value of 0.000 <0.05, the work motivation variable has a significant influence on employee performance, this is also evidenced by a value of 0.000 <0.05. Work environment variables and work motivation together have a significant effect on employee performance, this is evidenced by the results of 0.000 <0.05.\Keywords: Work Environment, Work Motivation and Employee Performance